PENGARUH PENERAPAN METODE DISKUSI DAN STRATEGI MENGAJAR GURU TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA DI MA AL URWATUL WUTSQO BULUREJO DIWEK JOMBANG TAHUN PELAJARAN 2023-2024 - Maulal Hikam Asshiddiqy; Suwandi Suwandi (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Educators should have the option to help and guide understudies in the growing experience with the goal that they can grasp their capacities and assets. One of the capacities that understudies should have is decisive reasoning. With decisive reasoning, understudies can build their imagination, settle on the ideal choices, foster their personality, see issues according to different perspectives, and in particular, become versatile. The purpose of this study is to determine three things: the impact of the discussion method on the critical thinking abilities of MA Al Urwatul Wutsqo Bulurejo Diwek Jombang students during the academic year 2023–2024; the impact of teachers' teaching strategies on the critical thinking abilities of MA Al Urwatul Wutsqo Bulurejo Diwek Jombang students during the academic year 2023–2024; and the impact of discussion methods and teacher teaching strategies on the students' critical thinking abilities This exploration utilizes a quantitative strategy utilizing corresponding separated irregular examining procedures. 127 students participated as respondents in this study. Multiple linear regression analysis and statistical tests were used to gather the data. The examination results show that: (1) Conversation strategies fundamentally impact understudies' decisive abilities to reason. The consequences of the speculation test show that the sig. 0.000 < 0.05 and the T count result is 5.032 > 1.979, so Ho is dismissed and Ha is acknowledged. (2) The hypothesis test demonstrates that the teaching method significantly influences students' capacity for critical thinking. The sig value is shown by the results. (3) The teacher's discussion techniques and teaching methods influence students' critical thinking abilities simultaneously and significantly. If 0.000 0.05 and the Tcount result is 3.576 > 1.979, then Ho is rejected and Ha is accepted. The sig value is shown by the calculated F value. 0.000 < 0.05 and sig esteem. 26.064 is greater than 3.07, indicating that Ha is accepted while Ho is rejected.